PERENCANAAN KAMPUNG WISATA DAGO POJOK SEBAGAI WISATA KREATIF BERBASIS KOMUNITAS LOKAL DI KOTA BANDUNG - Chairunnisa, Desy (2012)
Dago Pojok Tourism Village is one of tourist destinations which have concepts such as travel, education, and industry in order to raise the potential settlement areas as economic and cultural center. Dago Pojok Tourism Village officially opened on October 28th, 2011. Tourism activities in the village has not planned well, whereas it has tourism potential as creative tourism because it involving local people and tourists directly on its development process. Planning area will be expected to result in the addition of the number of tourist visits. The method used in this research is descriptive qualitative analysis, research that leads to solved problems as the disclosure, where the researcher acts as a key instrument. Data collection techniques performed with triangulation (combined), data analysis is inductive, and qualitative research results further emphasize the significance rather than generalizations. Related theories in support of this research include the concept of tourism, the tourism potential concept, the concept of regional planning, creative tourism concept, the concept of zoning, and the concept of community-based tourism. Interviews with the informants conducted to obtain accurate results regarding the operation of Dago Pojok Tourism Village, questionnaires to local people who are active in activities at Dago Pojok Tourism Village, and field observations were conducted to see factual conditons at Dago Pojok Tourism Village. From the results of the research showed that Dago Pojok Tourism Village has potential issues to be developed as creative tourism and has a good responses from local citizens. From the results based on descriptive analysis, it can be recommended for Dago Pojok Tourism Village planning as creative tourism based on local community in Bandung, by utilizing the existing potential, build partnerships with investors, and build adequate facilities and infrastructure